Photochromism of indolino-benzopyrans studied by NMR and UV-visible spectroscopy (International Journal of Photoenergy)
The synthesis of photochromic 3,3-di( 4 ′ -fluorophenyl)-3H-benzopyrans fused to an indole moiety is described. The structures of photomerocyanines elucidated by NMR spectroscopy and spectrokinetic data ( λ max⁡ of colored form, colorability, and rate constant of bleaching) obtained by UV-visible spectroscopy are reported.